Enterprise big data engineering, analytics, and management - Atzmüller, Martin; Oussena, Samia 1962-; Roth-Berghofer, Thomas R. 1967- (Advances in business information systems and analytics (ABISA) book series, 2016)
"This book presents novel methodologies and practical approaches to engineering, managing, and analyzing large-scale data sets with a focus on enterprise applications and implementation"...